2011
DOI: 10.5005/jp-journals-10012-1038
|View full text |Cite
|
Sign up to set email alerts
|

Medial Mandibular Flexure: A Review of Concepts and Consequences

Abstract: Mandible is a long bone which is bent in the form of a 'U' or bow, supported and articulated with the cranium by means of muscles and ligaments. These muscles, tendons and ligaments attached to the mandible exert force, which causes change in the shape of the mandible at different levels of movement of the jaws. A medial flexure of mandible occurs during wide opening of mouth with the amount of flexure depending on the degree of jaw movement. This mandibular flexure, though minimal, has a profound influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Medium mandibular deflection poses challenging problems for both conventional prostheses and implants. Biological and prosthetic complications related to high stress at the bone and prosthetic interface may cause loosening and fracture of the implant or prosthetic screws, chipping of the veneering material, and bone resorption around the implant [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Because of this situation, it is vitally important to contemplate it, try not to decrease its gap amplitude, and thus achieve successful, predictable treatments with suitable longevity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium mandibular deflection poses challenging problems for both conventional prostheses and implants. Biological and prosthetic complications related to high stress at the bone and prosthetic interface may cause loosening and fracture of the implant or prosthetic screws, chipping of the veneering material, and bone resorption around the implant [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Because of this situation, it is vitally important to contemplate it, try not to decrease its gap amplitude, and thus achieve successful, predictable treatments with suitable longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported increased biomechanical stress at the prosthetic and implant levels, poor passivity of fit, impression distortion, pain during function, de-cementation of the prosthesis, porcelain chipping, prosthetic screw loosening and fracture, bone resorption, and implant fracture [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Mandibular dimensional changes were investigated with transducers fixed on the tooth surface or implants, strain gauges, and intraoral optical surface scanning (IOS), as well as measuring plaster models and photographs at different stages of opening [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mandible flexes around the mandibular symphysis with medial pull on the mandibular condyles and sagittal movement of the posterior segments (2) . MMF in prosthetic treatments can increase stress in abutments, fixed prostheses, and removable prostheses, thereby causing distortion and pain during function, breakage of implant screws, loosening of prosthesis cement, and porcelain fracture (3) . The bending of the mandible can also affect the stability of the lower denture.…”
Section: Introductionmentioning
confidence: 99%
“…The mandibular deformation may range from a few micrometers to more than 1 mm (3,8) . Different methods used to evaluate and measure mandibular deformation include the following: intra-oral measuring techniques by calipers, gauges, strain gauges or transducers, extraoral measuring techniques by comparing diagnostic casts made from impressions taken at various openings of mandible and model simulations of three-dimensional finite element analysis (2,3,8) .…”
Section: Introductionmentioning
confidence: 99%